The integrative bioinformatics approaches to predict the xanthohumol as anti-breast cancer molecule: Targeting cancer cells signaling PI3K and AKT kinase pathway - Gupta, Kartikey Kumar; Sharma, Kamal Kant; Chandra, Harish; Panwar, Himalaya; Bhardwaj, Nitin; Altwaijry, Najla A.; Alsfouk, Aisha A.; Dlamini, Zodwa; Afzal, Obaid; Altamimi, Abdulmalik S. A.; Khan, Shahanavaj; Mishra, Abhay Prakash (Frontiers in Oncology, 2022)
Breast cancer is the most common type of cancer in women, vast research is being conducted throughout the world for the treatment of thus malignancy by natural products using various computational approaches. Xanthohumol, a prenylated flavonoid, is known for its anti-cancer activity, however, the mechanism behind its action is still in the preliminary stage. The current study was aimed to analyses the efficacy of Xanthohumol compared to the currently available anticancer drugs targeting Phosphoinositide-3-kinase (PI3K), Serine/Threonine kinase (AKT) receptors and human epidermal growth factor receptor 2 (HER2) for breast cancer treatment through in-silico analysis. The result revealed that the target compound showed significant binding affinity to target(s) within the PI3K, AKT and HER2 signaling pathway with a binding energy of -7.5, - 7.9 and -7.9 Kcal/mol, respectively. Further predictions study were then made concerning this compounds absorption, distribution, metabolism and excretion (ADME) as well as drug-likeness properties, resulting for its oral bioavailable with only a single violation of the Lipinski’s rule of five. The finding revealed the ability of Xanthohumol to bind with multiple cancer cell signaling molecules including PI3K, AKT kinase and HER2. The current novel study opened the door of advancing the research into the management and treatment of breast cancer.